2012
DOI: 10.1093/pubmed/fdr113
|View full text |Cite
|
Sign up to set email alerts
|

An overview of prevention of multiple risk behaviour in adolescence and young adulthood

Abstract: The observed clustering, and shared underlying determinants, of risk behaviours in young people has led to the proposition that interventions should take a broader approach to risk behaviour prevention. In this review we synthesized the evidence on 'what works' to prevent multiple risk behaviour (focusing on tobacco, alcohol and illicit drug use and sexual risk behaviour) for policy-makers, practitioners and academics. We aimed to identify promising intervention programmes and to give a narrative overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 58 publications
4
138
0
11
Order By: Relevance
“…If associations prove to be causally related, substance use prevention efforts have the potential to decrease the burden of teenage parenting and sexually transmitted infections in at-risk urban communities. Therefore, it is important that substance use prevention programs monitor their impact on sexual risk behavior as Jackson and colleagues [25] found that few interventions have evaluated their impact on both substance use and sexual risk behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If associations prove to be causally related, substance use prevention efforts have the potential to decrease the burden of teenage parenting and sexually transmitted infections in at-risk urban communities. Therefore, it is important that substance use prevention programs monitor their impact on sexual risk behavior as Jackson and colleagues [25] found that few interventions have evaluated their impact on both substance use and sexual risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Both intervention and control students are included in the analysis. These individuals had (1) first grade teacher ratings of behaviors and academic achievement, (2) at least one annual report of past year frequency of marijuana and alcohol use during grades 8-12, and (3) at least one assessment of outcomes during the 7-year period following high school (approximately ages [19][20][21][22][23][24][25]. Most of the sample (65.5%) participated in all five annual assessments in grades 8-12, whereas 63.5% participated in all seven assessments post high school graduation.…”
Section: Samplementioning
confidence: 99%
“…Yet, it is not clear whether the experience of (multiple) risks online can be traced back to the same common underlying risk factor shared with the experience of (multiple) risks offline and how much (if any) of adolescents' risk experience can be explained by the specific environment (offline vs. online). If a common factor were identified it could account for both online and offline risks and so aid the development of prevention strategies for online risks (Hale & Viner, 2012;Hale, Fitzgerald-Yau, & Viner, 2014;Jackson, Henderson, Frank, & Haw, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Individual school 1st line safe-net [ Figure 3] Intersectoral partnership of WEE project (Jackson, Geddes, Haw, & Frank, 2012;Jackson, Henderson, Frank, & Haw, 2012;Wells, Barlow, & Stewart-Brown, 2003). …”
Section: Wee Classmentioning
confidence: 99%